Experimental study using natural frequencies for fruit identification - Tantisopharak, T.; Krairiksh, M.; Sarkar, T. K. (My University, 2013)
This paper presents the experimental study for characterization of the ripening state of a fruit. The identification can be performed by comparing the libraries of natural poles, which can be extracted from its scattering response of the fruit. This experiment measures scattering responses from composite dielectric objects, and then applies the Cauchy method to extract the poles from the responses. Libraries of poles are catalogued to validate the identification System.
Keywords: Cauchy method; Natural poles; Resonances; Target identification